1985
DOI: 10.1128/jb.164.2.816-822.1985
|View full text |Cite
|
Sign up to set email alerts
|

Role of glnB and glnD gene products in regulation of the glnALG operon of Escherichia coli

Abstract: We have isolated insertion and deletion mutants in glnB, the structural gene of PI,, a member of the adenylylation system for glutamine synthetase of Escherichia coli, to study the role of PI, in the regulation of the synthesis of glutamine synithetase and of histidase in response to nitrogen deprivation or excess. We have studied the effects of this mutation alone and combined with nul mutations resulting from the insertion of transposons or from a deletion in the other genes affecting this regulation, ginD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(80 citation statements)
references
References 25 publications
6
73
1
Order By: Relevance
“…To analyze glnA expression in these transformants, the glutamine synthetase activity was determined, which is proportional to the amount of gZnA gene product. The vector controls exhibited similar glutamine synthetase activities to those reported previously for the non-transformed strains ( Table 2 ; Bueno et al, 1985). Compared with the parental strain YMC10, the glnB mutant RB9060 exhibited elevated glutamine synthetase levels in the nitrogen-excess medium.…”
Section: Modification Of Synechococcus P By Uridylylation In E Colisupporting
confidence: 78%
See 1 more Smart Citation
“…To analyze glnA expression in these transformants, the glutamine synthetase activity was determined, which is proportional to the amount of gZnA gene product. The vector controls exhibited similar glutamine synthetase activities to those reported previously for the non-transformed strains ( Table 2 ; Bueno et al, 1985). Compared with the parental strain YMC10, the glnB mutant RB9060 exhibited elevated glutamine synthetase levels in the nitrogen-excess medium.…”
Section: Modification Of Synechococcus P By Uridylylation In E Colisupporting
confidence: 78%
“…For cloning experiments, ligations were transformed in competent E. coli DH5a cells, which were grown in Luria-Bertani medium (Sambrook et al, 1989). For the physiological analysis of E. coli cells expressing the Synechococcus gEnB gene, cells were grown either under nitrogen excess (Luria-Bertani medium containing 0.2% glutamine and 0.4% glucose) or in nitrogen-limiting minimal medium containing either 0.2 % glutamine and 0.4 % glucose or 0.2% arginine and 0.4 % glucose as described by Bueno et al (1985).…”
mentioning
confidence: 99%
“…F13202 carries a transposon insertion in ntrC and a deletion of glnB, the structural gene for the PII protein. PIT is a negative regulator of NtrC-P, together with the histidine kinase NtrB, it stimulates the dephosphorylation of NtrC-P under conditions of nitrogen excess (Bueno et al, 1985;Ninfa and Magasanik, 1986;Keener and Kustu, 1988;Atkinson et al, 1994). F13202 lacks glnB, resulting in the constitutive phosphorylation of the introduced NtrC hybrid proteins.…”
Section: Resultsmentioning
confidence: 99%
“…A virulent derivative of phage P1 was used for all transductions. Strains were grown in LB medium (Miller, 1972), GLBgln, GNgln (Bueno et al, 1985), PNgln (Feng et al, 1992) or MOPS minimal medium supplemented with 10 mM K2HPO4 for phosphate excess or 0.1 mM K2HPO4 for phosphate limitation conditions (Neidhardt et al, 1974), as indicated in the figure legends. All media contained 10 ,ug/ml kanamycin, 5 ,ug/ml tetracycline or 100 gg/ml ampicillin when appropriate.…”
Section: Bacterial Strains Bacteriophages and Growth Conditionsmentioning
confidence: 99%
“…From the P II protein, the signal is transferred to ATase, which regulates GS activity. Two P II -type proteins are present in E. coli: the products of glnB (Bueno et al, 1985;van Heeswijk et al, 2009) and glnK (van Heeswijk et al, 1995(van Heeswijk et al, , 1996. P II and GlnK form heterotrimers that are proposed to be important for fine tuning the nitrogen regulatory cascade (van Heeswijk et al, 2000).…”
Section: Introductionmentioning
confidence: 99%